Evaluation of antimicrobial consumption in Campania Region, Italy - Simona Cammarota; Anna Citarella; Enrica Menditto; Simona de Portu (Farmeconomia: Health Economics and Therapeutic Pathways, 2008)
Introduction: the antibiotic usage in Italy is above the European average. From several years the Campania was the first Italian region in terms of antimicrobial consumption. Aim: to evaluate antibiotic utilisation in primary health care in Campania, a region of approximately 5.7 million inhabitants in the south of Italy. Method: we collected, from an electronic database, all prescription drugs reimbursed in 2005. The cohort was defined as the population of subjects receiving at least one prescription of any antimicrobial agent for systemic use, classified according to their therapeutic role using Anatomic Therapeutic Chemical (ATC) classification. Drugs cost and consumption were quantified using National Health Service (NHS) prospective and Defined Daily Dose system (DDD) respectively. All costs were expressed in Euro 2005. Results: antiinfectives agents (ATC J) was the second class of drugs in terms of cost, representing 16.1% of the regional drug expenditure. Their consumption were 33 DDD/1000 inhabitants/day. Stratifying by age antibiotic use was highest in children and elderly subjects. Penicillins, macrolides and cephalosporins were the most prescribed antibiotic classes in all age groups. Discussion: despite guidelines introduced to limit the prescription of parenteral antibiotics to the patients who are most likely to benefit from it, they were mostly prescribed. This represented a serious problem for the development of drug-resistant bacteria.